Perspektif Kritis tentang Pembelajaran Sosial-Emosional dalam Pendidikan Nonformal: Meningkatkan Kesejahteraan di Kalangan Komunitas Marginal - Yudistira, Satria (PAKAR Pendidikan, 2025)
Nonformal education is crucial in accessing marginalized communities often excluded from formal education systems. However, integrating Social-Emotional Learning (SEL) approaches in nonformal education remains limited. This study aims to explore the role of SEL in enhancing the psychological, social, and emotional well-being of learners from marginalized communities and identify implementation challenges. The research employs a literature review method with a critical analysis of SEL theories and practices and their relevance to nonformal education contexts. The findings indicate that the application of Social and Emotional Learning (SEL) in nonformal education has significant potential to improve the welfare of marginalized communities, especially in the context of education at Community Learning Activity Centers (PKBM) and other learning groups. However, the study also reveals structural, social, and cultural barriers, including a lack of policy support and resource limitations. This study concludes that integrating SEL into nonformal education holds substantial potential to improve the quality of life for marginalized communities. Therefore, inclusive policy support, facilitator training, and culturally adaptive approaches are essential. This research contributes to developing education science, particularly in creating holistic nonformal education models to enhance community well-being.